Geothermal Energy Science – Society – Technology - Kolditz, Olaf; Huenges, Ernst; Kohl, Thomas; Moeck, Inga S.; Gutiérrez-Negrín, Luis Carlos
Geothermal Energy – Science, Society and Technology focuses on fundamental and applied research needed to deploy technologies for developing and integrating geothermal energy as one key element in the future energy portfolio. Contributions include geological, geophysical, and geochemical studies, exploration of geothermal fields, reservoir characterization and modeling, development of productivity-enhancing methods, and approaches to achieve robust and economic plant operation. Geothermal Energy – Science, Society and Technology serves to examine the interaction of individual system components while taking the whole process into account, from the development of the reservoir to the economic provision of geothermal energy.